DEVELOPMENT OF KALAM SCIENCE IN INDONESIA - Mahdi Handayani Sidik (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The article discussing the development of kalam science in Indonesia serves as a fundamental framework in understanding the Islamic intellectual history in this region. Through a comprehensive historical overview, the article delineates the evolution of kalam science over time, elucidating the pivotal roles played by key figures in religious thought. This mapping also encompasses philosophical discussions, divergent viewpoints, and the social and religious implications for Indonesian society. This exploration provides profound insights into how kalam science influences perceptions, beliefs, and religious practices within Indonesian communities. In a broader context, the article depicts how kalam science contributes to the diversity and harmony of religious life in Indonesia, highlighting its significant role in intellectual diversity and religious life in the country